2015
DOI: 10.1136/bmjopen-2015-008096
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to guidelines on antibiotic treatment for respiratory tract infections in various categories of physicians: a retrospective cross-sectional study of data from electronic patient records

Abstract: ObjectiveTo study how prescription patterns concerning respiratory tract infections differ between interns, residents, younger general practitioners (GPs), older GPs and locums.DesignRetrospective study of structured data from electronic patient records.SettingData were obtained from 53 health centres and 3 out-of-hours units in Jönköping County, Sweden, through their common electronic medical record database.ParticipantsAll physicians working in primary care during the 2-year study period (1 November 2010 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 12 publications
4
29
0
Order By: Relevance
“…In the United States, the prescriptions of antibiotics for children with URI has decreased in these years [ 26 , 27 , 28 ]. Intervention by strict criteria, enforcement of national guidelines and community-wide campaign could have influences in antibiotics prescribing for children [ 29 , 30 , 31 ]. However, the low overall consumption of antibiotics is by no means an indicator of appropriate pediatric antibiotic prescribing [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, the prescriptions of antibiotics for children with URI has decreased in these years [ 26 , 27 , 28 ]. Intervention by strict criteria, enforcement of national guidelines and community-wide campaign could have influences in antibiotics prescribing for children [ 29 , 30 , 31 ]. However, the low overall consumption of antibiotics is by no means an indicator of appropriate pediatric antibiotic prescribing [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] Studies have shown poor guideline adherence for respiratory problems, [7][8][9][10] urinary tract infections, [11,12] tonsillitis [13] and acute diarrhoea. [10] Other variables associated with poor adherence include seniority of the clinician, [14] prescriber workload, [15] patient age [8,14] and area-level socioeconomic status. [8] Using antibiotics incorrectly and inappropriately by not following guidelines can contribute to the development of resistance, as well as poor clinical outcomes including patient morbidity.…”
Section: Researchmentioning
confidence: 99%
“…Indeed, several authors have shown that older PCPs tend to have lower adherence to recent guidelines. [ 34 , 35 ]…”
Section: Discussionmentioning
confidence: 99%